Photoluminescence and optical properties of nanostructure Ni doped ZnO thin films prepared by sol-gel spin coating technique - Farag, A. A. M.; Cavas, M.; Yakuphanoğlu, Fahrettin; Amanullah, F. M. (Elsevier Science Sa, 2011)
In this work, the spin coating sol-gel technique has been successfully used to deposit highly uniform and good adhesion of nano structure thin films of ZnO doped with different Ni concentrations. The morphological properties of ZnO: Ni films were studied by atomic force microscopy (AFM) technique. The surface morphology of the nanostructure films is found to depend on the concentration of Ni. The effects of Ni contents on the structural and photoluminescence (PL) properties of ZnO films were investigated. Optical constants (refractive index, n, and absorption index, k) of the undoped and Ni-doped ZnO of 0.2%, 0.4%, 0.6%, 0.8%, 1%, 3%, 5% and 7% concentrations have been obtained in the wavelength range 200-1000 nm by using spectrophotometric measurements. The dispersion parameters were determined and discussed based on the single oscillator model. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ni-doped ZnO; Nanostructure thin film; Optical constants; Sol-gel; Spin coating